Behavior of parents and educators following traumatic injury to young permanent teeth of children in Joinville, Santa Catarina - Jennyffer Samira de Lima; Jaini Dalprá; Susimara Braga de Almeida (Revista Sul-Brasileira de Odontologia, 2019)
Traumatic dental injuries are a major public health problem, especially in the age range of 7 to 15 years, when young permanent teeth are established. Objective: To evaluate the behavior of parents of children who attend public or private school and their educators, in cases of traumatic injury to young permanent teeth and to evaluate whether they sought emergency guidance, in the city of Joinville, Santa Catarina, Brazil. Evaluation was carried out via a questionnaire for asking the parents and teachers about their knowledge of dental trauma. Material and methods: A total of 248 parents and 22 teachers participated in the study. Out of all the participants that completed the questionnaire with questions on previous trauma experience, avulsion behavior, avulsed tooth storage medium, and time elapsed from dental trauma until care, 49.6% of had higher education. The data were tabulated on a Microsoft Office Excel 365 worksheet, and the chi-square statistical test was applied. Results: The research showed that 91.8% of parents and 8.2% of educators from both public and private schools had minimal knowledge regarding dental trauma. Many of the participants (73.2%) were unaware of what dental reimplantation was and lacked knowledge regarding storage choices for a dental element. Instead, 68% preferred to take the child to a dental surgeon to receive emergency care. Conclusion: The knowledge parents and educators of public and private schools have about dental trauma is limited. Education on this subject needs to be promoted for enabling parents and educators to make informed decisions to ensure the best prognosis after traumatic dental injury.